DEPRESSION AMONG COLLEGE STUDENTS - Ratu, Bau; Elfira, Ninil; _, Sukma; Sirumpa, Yuyun Lestari; Andini, Fitra; Sateki, Kristanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2025)
Depression among college students has become a significant mental health issue, with an average prevalence reaching 30.6%. This study aims to comprehensively examine the phenomenon of depression among college students, its impacts, and effective prevention and intervention strategies. Using a systematic review method, this study analyzes literature from databases such as PubMed, PsycINFO, and Google Scholar. The results show that depression in college students seriously affects academic performance, social interactions, substance abuse, sleep disorders, and the risk of suicide. Various effective interventions have been identified, including cognitive behavioral therapy, hypnofivesics, logotherapy, empathy interventions, physical activity, and, in certain cases, drug therapy. A holistic approach combining psychological therapy, spiritual aspects, and social support is considered most effective. This study highlights the importance of mental health awareness, access to mental health services on campus, and the active role of educational institutions in supporting students' mental well-being. Suggestions for future research include longitudinal studies and evaluating the effectiveness of interventions in diverse cultural contexts.